Population density and social organisation of the Cape clawless otter, Aonyx Capensis Schinz, in the Tsitsikama Coastal National Park. - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1983.